(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Twenty-two morphometric and nine meristic characters of 280 Gudusia chapra (Total length 30-210mm) and 264 Gonialosa manmina (Total length 40-150 mm), the two important clupeids from the Kaptai lake, were studied during 1996-1997 to detect the plastic and non-plastic characters. Wide and medium range characters are plastic characters and hence are controlled by the environment while the narrow range characters are genetically controlled and non-plastic and hence can be used for differentiation of stock or sub-species. Three different categories of morphometric characters of the two species were recognised, viz., wide range, medium range and narrow range. Wide range morphometric characters varied within the range of 21.47% to 140.62% in the case of G. chapra and 24.04% to 87.19% in the case of G. manmina while the medium range characters varied within the range of 11.76% to 13.75% in the case of G. chapra and 11.55% to 18.92% in the case of G. manmina and less than 10% range characters were designated as narrow range. The relationships between the different morphometric characters (both dependent and independent variables) were found to be linear and in all the cases the relationships were found to be highly significant (P< 0.001). DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13403 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):21-31, 2008